2021
DOI: 10.1038/s41598-021-00955-7
|View full text |Cite
|
Sign up to set email alerts
|

The chemotherapeutic drug carboplatin affects macrophage responses to LPS and LPS tolerance via epigenetic modifications

Abstract: Following re-exposure to lipopolysaccharide (LPS), macrophages exhibit an immunosuppressive state known as LPS tolerance, which is characterized by repressed proinflammatory cytokine production. LPS-induced tolerance in macrophages is mediated in part by epigenetic changes. Carboplatin, an anticancer chemotherapeutic drug, exerts its effect by inhibiting DNA replication and transcription, as well as through epigenetic modifications. Through an unbiased screen, we found that carboplatin rescued TNF-α and IL-6 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The E2F signaling pathway and the G2M checkpoint are also involved in platinum resistance. [54,55] In this study, GSEA analysis showed that ELOVL6 is involved in the E2F signaling pathway, G2M checkpoint, MTORC1 signaling pathway, apoptosis, PI3K-AKT-MTOR signaling pathway and P53 signaling pathway, suggesting that ELOVL6 may play an important role in regulating various cellular functions such as cell cycle, proliferation, metabolism, and survival. [56–59] Among them, the E2F signaling pathway, G2M checkpoint, PI3K-AKT-MTOR signaling pathway and P53 signaling pathway are involved in tumor resistance to EGFR-TKI and platinum-based drugs, respectively.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The E2F signaling pathway and the G2M checkpoint are also involved in platinum resistance. [54,55] In this study, GSEA analysis showed that ELOVL6 is involved in the E2F signaling pathway, G2M checkpoint, MTORC1 signaling pathway, apoptosis, PI3K-AKT-MTOR signaling pathway and P53 signaling pathway, suggesting that ELOVL6 may play an important role in regulating various cellular functions such as cell cycle, proliferation, metabolism, and survival. [56–59] Among them, the E2F signaling pathway, G2M checkpoint, PI3K-AKT-MTOR signaling pathway and P53 signaling pathway are involved in tumor resistance to EGFR-TKI and platinum-based drugs, respectively.…”
Section: Discussionmentioning
confidence: 80%
“…[56–59] Among them, the E2F signaling pathway, G2M checkpoint, PI3K-AKT-MTOR signaling pathway and P53 signaling pathway are involved in tumor resistance to EGFR-TKI and platinum-based drugs, respectively. [54,55,60–63] This suggests that up-regulation of ELOVL6 may mediate the development of associated drug resistance through the signaling pathways described above.…”
Section: Discussionmentioning
confidence: 99%
“…The tolerance-reversing and priming effects of MEK1/2-ERK inhibition are reminiscent of the effects induced by ultra-low doses of LPS [37][38][39], BCG vaccine [40], C. albicans [41] and its cell wall component β-glucan [4,42], oxidized low-density lipoprotein (ox-LDL) [43,44], and the antineoplastic agent known as carboplatin [45]. These stimuli commonly reverse LPS tolerance and/or train/prime macrophages through epigenetic reprogramming.…”
Section: Discussionmentioning
confidence: 99%
“…Toll-like receptors (TLRs) exposed to bacterial endotoxin, such as LPS, induce the transient silencing of a subset of genes, including those encoding proinflammatory mediators, and exhibit a transient immunosuppressive state upon recurrent stimulation with LPS (“LPS tolerance”). This is one of the most important mechanisms that protects the host from dysregulated inflammation ( Foster et al, 2007 ; López-Collazo and del Fresno, 2013 ; Boonmee et al, 2021 ). Foster et al showed that several hundred genes, including those encoding antimicrobial effectors, induced by the initial exposure to LPS stimulation, exhibit enhanced expression upon subsequent LPS stimulation.…”
Section: Transcriptional Memory: Possible Contributor To Late-onset D...mentioning
confidence: 99%